RELASI MASYARAKAT MARGINAL SEBAGAI LIYAN DALAM KONFLIK AGRARIA DI INDONESIA DALAM PERSPEKTIF LIYAN SEBAGAI ORANG KETIGA ARMADA RIYANTO - Rex Firenze Tonta (Masokan Ilmu Sosial dan Pendidikan, 2023)
This article aims to identify patterns of relations between marginalized communities (indigenous communities, farmers, etc.) and the state (government, regulations, officials) in agrarian conflicts in Indonesia. This article uses Armada Riyanto's thinking about "others as third people" as a basis for analyzing relations in agrarian conflicts between society and the state. The finding in this article is that the other as a third person in the agrarian conflict in Indonesia, which is occupied by marginalized communities, is not something natural, but is produced either from historical deposits or hegemonic residue in the discriminatory Dutch colonial agrarian policies in the domain verklaring. Or through formalization in language grammar and everyday experience which creates an isolating zone for others, so that the possibility of participation disappears. The state has more authority because it has many instruments, such as regulating regulations and enforcing them, which have the potential to formalize and perpetuate discrimination. Although regulations are still needed as a guarantee and legality to protect citizens' rights to their land, they can be a means of recognizing land for communities that have been marginalized. So whatever development program is carried out by the government based on the aim of improving the welfare of society and the environment needs to be supported. However, on the other hand, it must still consider or be sensitive to marginalized community groups who often become "victims" in the name of development. Tujuan artikel ini untuk mengidentifikasi pola relasi antara masyarakat marginal (masyarakat adat, petani dll.) dan negara (pemerintah, regulasi, aparat) dalam konflik agraria di Indonesia. Artikel ini menggunakan pemikiran Armada Riyanto tentang “liyan sebagai orang ketiga” sebagai landasan untuk menganalisis relasi dalam konflik agraria antara masyarakat dan negara. Temuan dalam artikel ini adalah liyan sebagai orang ketiga dalam konflik agraria di Indonesia yang ditempati oleh masyarakat marginal, bukanlah sesuatu yang kodrati, melainkan dihasilkan baik dari endapan historis atau residu hegemonik dalam kebijakan diskriminatif agraria kolonial Belanda dalam domein verklaring. Maupun melalui formalisasi dalam gramatika bahasa dan pengalaman sehari-hari yang menciptakan zona isolatif bagi liyan, sehingga kemungkinan partisipasinya lenyap. Kewenangan lebih yang dimiliki negara karena punya banyak instrumen seperti mengatur regulasi juga penegakannya berpotensi untuk melakukan formalisasi dan melanggengkan diskriminasi. Walaupun regulasi tetap dibutuhkan sebagai jaminan dan legalitas untuk melindungi hak warga negara atas tanahnya, hal itu dapat menjadi sarana pengakuan atas tanah bagi masyarakat yang selama ini termarginalkan. Jadi apapun program pembangunan yang dilakukan oleh pemerintah yang didasarkan pada tujuan ingin menyejahterakan masyarakat dan lingkungannya perlu didukung, namun di lain pihak tetap harus mempertimbangkan atau memiliki kepekaan terhadap kelompok masyarakat marginal yang seringkali menjadi “korban” atas nama pembangunan.